1990
DOI: 10.1161/01.str.21.9.1318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of normothermic versus mild hyperthermic forebrain ischemia in rats.

Abstract: We compared the neuropathological consequences of global forebrain ischemia under normothermia versus mild hyperthermia. Twenty-one rats underwent 20 minutes of four-vessel occlusion during which brain temperature was maintained at either 37° C (normothermia, n=9) or 39° C (hyperthermia, n=12). Quantitative neuropathological assessment was conducted 1 or 3 days later. At 1 day following the ischemic insult, normothermic rats demonstrated neuronal injury mainly confined to the most dorsolateral striatum. By 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
2
6

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(116 citation statements)
references
References 31 publications
(13 reference statements)
6
100
2
6
Order By: Relevance
“…Результаты доклинических исследова-ний свидетельствуют о наличии взаимосвязи между гипертермией и исходом инсульта, и, согласно надеж-ным экспериментальным данным, гипертермия усу-губляет ишемическое повреждение головного мозга [5][6][7]. В качестве независимого прогностического маркера лихорадку (температуру тела >38°C) вклю-чили в валидизированные прогностические модели для прогнозирования летальности и функциональ-ного исхода после острого ишемического инсульта [8,9].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Результаты доклинических исследова-ний свидетельствуют о наличии взаимосвязи между гипертермией и исходом инсульта, и, согласно надеж-ным экспериментальным данным, гипертермия усу-губляет ишемическое повреждение головного мозга [5][6][7]. В качестве независимого прогностического маркера лихорадку (температуру тела >38°C) вклю-чили в валидизированные прогностические модели для прогнозирования летальности и функциональ-ного исхода после острого ишемического инсульта [8,9].…”
Section: Discussionunclassified
“…Data from preclinical studies provided a link between hyperthermia and stroke outcomes, and robust experimental evidence for detrimental effects of hyperthermia on ischemic brain injury is available. [5][6][7] Fever (temperature Ͼ38°C) has been included as an independent prognostic marker in validated prognostic models for prediction of mortality and functional outcome after an acute ischemic stroke. 8,9 A recent meta-analysis suggested that pyrexia after stroke was significantly associated with mortality and morbidity.…”
mentioning
confidence: 99%
“…Because such a therapy was not used in any thermoregulatory study in the past (Table 1), some animals were likely to die in those studies. Knowing that even mild hyperthermia strongly exaggerates neural damage and increases the related mortality rate (15), it is reasonable to suspect that hyperthermic animals were more likely to die after OVLT lesioning than normo-or hypothermic animals in the early studies.…”
Section: Hyperthermia Induced By Ovlt Lesionmentioning
confidence: 99%
“…Hypothermia during HI has been shown to prevent or delay HI brain injury (9,(13)(14)(15)(16)(17). However, evidence for a potential beneficial effect of postinsult hypothermia in neonatal animal models of HI has been conflicting, with studies showing varying degrees of protection for different periods and depths of hypothermia (18 -20).…”
mentioning
confidence: 99%